A shorter commentary on Romans - Barth, Karl (Richmond, Virginia John Knox Press, 1959)
"This short commentary is the smaller and younger brother of the Epistle to the Romans of 1918 and 1921. It originated as the manuscript for a course of extra-mural lectures held in Basle during the winter of 1940-1." - From the Preface.
Keywords: Bible. -- Romans -- Commentaries. Bible. -- Romans